Physiological studies on carboxymethyl cellulase formation by Aspergillus terreus DSM 826 - Abdel-Fatah,Osama M. (2012)
Physiological studies were conducted to determine the optimum cultural conditions for maximal carboxymethyl cellulase (CMCase) formation by Aspergillus terreus DSM 826. Shaking condition at 150 rpm is favorable for the production of CMCase from rice straw and sugar cane bagasse. The highest enzyme yield was obtained at the third day of incubation at 30ºC for both cases; however CMCase formation occurred at a broad range of pH values, with maximal formation of A. terreus DSM 826 CMCase at pH 4.5 and 5.0 when rice straw and sugar cane bagasse were used as sole carbon source, respectively. Carboxymethyl cellulose (CMC) was found to be a good inducer for CMCase formation in both agricultural wastes with CMC concentrations of 0.5 and 1.0 % (w/v) in case of rice straw and sugar cane bagasse, respectively. High level of enzyme formation was obtained with the addition of ammonium chloride as nitrogen source in both cases and at a concentration of 0.4 % (v/v Tween-80) as an addition to medium containing rice straw. However this addition did not influence the production of CMCase in case of using sugar cane bagasse as carbon source.